2007
DOI: 10.1088/0031-9155/52/8/n01
|View full text |Cite
|
Sign up to set email alerts
|

Front-illuminated versus back-illuminated photon-counting CCD-based gamma camera: important consequences for spatial resolution and energy resolution

Abstract: Charge-coupled devices (CCDs) coupled to scintillation crystals can be used for high-resolution imaging with x-rays and gamma rays. When the CCD images can be read out fast enough, the energy and interaction position of individual gamma quanta can be estimated by a real-time image analysis of the scintillation light flashes ('photon-counting mode'). The electron-multiplying CCD (EMCCD) is well suited for fast read out, since even at high frame rates it has extremely low read-out noise. Back-illuminated (BI) EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 29 publications
(26 reference statements)
1
37
0
Order By: Relevance
“…In previous studies of this nature it is often the case that the peak signal (or sum of 3 × 3 pixels) of a photon flash is assumed to be proportional to the energy of the incident X-ray [1,2,10]. Ignoring the depth of interaction effects (discussed later) this would be the case for unity gain.…”
Section: Limitations For Photon-countingmentioning
confidence: 99%
“…In previous studies of this nature it is often the case that the peak signal (or sum of 3 × 3 pixels) of a photon flash is assumed to be proportional to the energy of the incident X-ray [1,2,10]. Ignoring the depth of interaction effects (discussed later) this would be the case for unity gain.…”
Section: Limitations For Photon-countingmentioning
confidence: 99%
“…Here we only summarize its characteristics; a comprehensive description of this gamma camera is provided elsewhere , Heemskerk et al 2007. Gamma photons are captured in the scintillation crystal and the light flashes that are generated are detected by a back-illuminated EMCCD.…”
Section: Emccd Read-out Electronics and The Photon-counting Algorithmmentioning
confidence: 99%
“…It has been shown that very high spatial resolutions (below 100 μm) can be obtained with a detector consisting of CsI(Tl) micro-columnar scintillation crystals read-out by a CCD operating at high frame rates (e.g. Beekman and De Vree 2005, Teo et al 2006, Meng 2006, Heemskerk et al 2007, Soesbe et al 2007, Westra et al 2009. However, due to the low capture efficiency of CsI(Tl) and the limited thickness of available micro-columnar crystals, these crystals are not well suited for small-animal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…De Vree et al (2005), Miller et al (2006), Nagarkar et al (2006), Heemskerk et al (2007), Meng and Fu (2008), Westra et al (2009)). To improve the applicability for medical imaging, the application of continuous (or monolithic) crystals can improve the sensitivity for incoming 99m Tc gamma photons (140 keV) at some cost in spatial and energy resolution (Korevaar et al 2009a, Heemskerk 2010.…”
Section: Introductionmentioning
confidence: 99%